Моделювання природного освітлення виробничих приміщень на основі аналітичного методу розрахунку геометричного КПО - Кіт, А. Ю.; Кіт, Ю. В.; Комаров, В. І. (Видавництво Національного університету «Львівська політехніка», 2009)
Unlike the graphic method of Дanylyuk, the analytical method of calculation of coefficient of natural illumination which development of mathematical model and computer-aided design of natural illumination is possible on the basis of is offered.
Keywords: labour protection; terms of labour; illumination; mathematical model